Research Methods for Dissertations on the Architecture Doctoral Program - Andadari, Tri Susetyo (Architecture Study Program, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2025)
The output produced by a student at the high program level is a dissertation. This phenomenon is present in almost all universities at the undergraduate, graduate and postgraduate program level, which requires students to master the philosophy of science as a compulsory course. The foundation is to search for science using logic, epistemology, and methodology. Many research methods can be used in a dissertation, depending on the research topic and the concept of the research paradigm. With the literature study method, this paper aims to provide an overview of the research methods commonly used in dissertation, especially for architectural doctoral programs. The point of view includes understanding, the outline of philosophical thinking and concepts, writing goals and steps, and examples of architectural methods.